2020
DOI: 10.31820/pt.29.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Emotion Regulation and Attitudes towards Risky Driving in a Group of Pre-Licensed Drivers

Abstract: Over-representation of novice drivers in motor-vehicle crashes encourages researchers to look for all possible psychological causes which might be targeted in prevention. The present study is aimed to explore the associations between difficulties in emotional regulation and attitudes towards risk-taking while driving in a group of pre-licensed drivers. The sample involved 475 driver’s licence candidates who completed the self-reported questionnaire with the Difficulties in Emotion Regulation Scale (DERS) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, the results show that the types of difficulties have distinctive effects on risky behaviors, including driving. Žardeckaitė-Matulaitienė et al (2020) found that a lack of emotional awareness was positively associated with a positive attitude toward violations, speeding, and drunk driving, but negatively associated with a positive attitude toward showing off; the other five difficulties were all positively associated with a positive attitude toward speeding, drunk driving, showing off, inobservance, and joyriding. According to Sani et al (2017), the five dimensions other than a lack of emotional clarity were positively associated with errors and violations.…”
Section: Difficulties In Emotion Regulation and Driving Behaviormentioning
confidence: 93%
See 1 more Smart Citation
“…However, the results show that the types of difficulties have distinctive effects on risky behaviors, including driving. Žardeckaitė-Matulaitienė et al (2020) found that a lack of emotional awareness was positively associated with a positive attitude toward violations, speeding, and drunk driving, but negatively associated with a positive attitude toward showing off; the other five difficulties were all positively associated with a positive attitude toward speeding, drunk driving, showing off, inobservance, and joyriding. According to Sani et al (2017), the five dimensions other than a lack of emotional clarity were positively associated with errors and violations.…”
Section: Difficulties In Emotion Regulation and Driving Behaviormentioning
confidence: 93%
“…Žardeckaitė‐Matulaitienė et al. (2020) found that a lack of emotional awareness was positively associated with a positive attitude toward violations, speeding, and drunk driving, but negatively associated with a positive attitude toward showing off; the other five difficulties were all positively associated with a positive attitude toward speeding, drunk driving, showing off, inobservance, and joyriding. According to Sani et al.…”
Section: Introductionmentioning
confidence: 99%